A Review of The Effectiveness of Fish Aggregating Devices (FADs) in Indonesian Waters - Afrisal, Muhammad; Masrurah Ismail; Ahmad Yani (Hasanuddin University, 2024)
The utilization of Fish Aggregating Devices (FADs) in fisheries represents one of the most attractive and effective methods for increasing fishermen's catches. This review article aims to evaluate the use of FADs in enhancing sustainable catch outcomes and considers their role as an effective management tool. Various types of FADs have been designed and developed across different waters in Indonesia. There are several types of FADs commonly observed, including Squid FADs, Bio FADs, Sea urchins FADs, Electronic FADs, Bamboo raft FADs, Coconut leaf attractor FADs, Palm fiber attractor FADs, Light attractor FADs, FADs palm midrib, Rafia rope attractor FADs, Lubuk larangan FADs, and Fiber FADs. This paper reviews the different types of FADs, considering aspects such as the catch produced, technical specifications, and economic factors. Among these, portable FADs constructed from coconut leaves and raffia lines as attractors emerge as particularly effective and commonly used in Indonesian waters. FADs are also often combined with lift nets or electric fish attractors to enhance their effectiveness. Environmentally friendly fishing gears such as handlines and fishing rods are commonly operated around FADs. The types of fish caught typically include a mix of small and large pelagic species.